Primary prevention of sexually transmitted infections in Switzerland: practices of family physicians and their determinants—a national cross-sectional survey - Hanna Vautrin; Nicolas Senn; Christine Cohidon (BMJ Open)
Objectives To describe the activities of general practitioners (GPs) pertaining to primary prevention in the field of affective and sexual life, studying the advice they provide as well as their vaccination practices.Design Cross-sectional national survey.Setting/participants The study was carried out using the Swiss Primary Care Active Monitoring GPs’ network, a national GP network created in 2012. One hundred and seventy Swiss GPs, from a random sample from professional lists stratified by canton, participated in the present study.Primary and secondary outcome measures Prevention practices against sexually transmitted infections (STIs) performed by GPs through advice provided as well as their vaccination practices. Predictive factor of these practices through their links with the doctors’ relevant characteristics and their opinions about STI prevention.Results Approximately 80% consider prevention in the area of affective and sexual life to be part of their duty and discuss it easily with patients. Most of them spontaneously give advice regarding STIs during a routine consultation. Regarding human papillomavirus (HPV) immunisation in adults, almost half of GPs report never doing it, while almost 75% often or always immunise their adult patients against hepatitis B. Higher numbers of consultations per day are associated with vaccinating more adults against HPV (OR 1.13 (1.05 to 1.23)) and against hepatitis A (OR 1.17 (1.05 to 1.31)). Vaccinating children against hepatitis B is associated with practising in rural areas (OR 4.64 (1.20 to 17.98)). GPs practising in the French-speaking region of Switzerland immunise children less against HPV (OR 0.40 (0.20 to 0.80)). Longer consultations are associated with providing advice on affective and sexual life during a first consultation (OR 1.08 (1.01 to 1.14)).Conclusion Swiss GPs are involved in primary prevention against STIs and consider it as their responsibility. Prevention practices are associated with GPs’ favourable opinions on prevention.